2020
DOI: 10.1002/jclp.23099
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ICD‐11 personality trait domain qualifiers with the MMPI‐2‐RF

Abstract: Objective The current study examined the utility of the Minnesota Multiphasic Personality Inventory‐2‐Restructured Form (MMPI‐2‐RF) in assessing ICD‐11 personality psychopathology trait domain qualifiers. Method Using a community sample (N = 217) weighted for externalizing dysfunction, this study evaluated the convergence between ICD‐11 trait domains as measured by the personality inventory for DSM‐5 (PID‐5) with hypothesized MMPI‐2‐RF scales. Particular emphasis was placed on evaluating the convergence betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Previous research utilizing the MMPI-2-RF found somewhat mixed results regarding the Anankastia domain and MMPI-2-RF externalizing scales; Anderson and Sellbom (2021) also observed a lack of association between MMPI-2-RF externalizing scales and the Anankastia domain, Carnovale and colleagues (2020) found only a weak negative association between Disconstraint (DISC) and Anankastia, but Tarescavage and Menton (2020) found moderate negative associations between Disconstraint and Anankastia. Anderson and Sellbom (2021) highlighted difficulty with the MMPI-2-RF scales in differentiating the Negative Affectivity and Anankastia domains, given the lack of associations of the Anankastia domain with low disinhibition scales. Therefore, the MMPI-3 appears to be better situated than the MMPI-2-RF for the assessment of the Anankastia domain and perfectionistic-type symptomatology given the addition of the Compulsivity (CMP) scale, which emerged as the best predictor of Anankastia domain scores, showing meaningful associations with individual CAT-PD traits such as Perfectionism, Rigidity and Workaholism, and thus being the main differential indictor of Anankastia from Negative Affectivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research utilizing the MMPI-2-RF found somewhat mixed results regarding the Anankastia domain and MMPI-2-RF externalizing scales; Anderson and Sellbom (2021) also observed a lack of association between MMPI-2-RF externalizing scales and the Anankastia domain, Carnovale and colleagues (2020) found only a weak negative association between Disconstraint (DISC) and Anankastia, but Tarescavage and Menton (2020) found moderate negative associations between Disconstraint and Anankastia. Anderson and Sellbom (2021) highlighted difficulty with the MMPI-2-RF scales in differentiating the Negative Affectivity and Anankastia domains, given the lack of associations of the Anankastia domain with low disinhibition scales. Therefore, the MMPI-3 appears to be better situated than the MMPI-2-RF for the assessment of the Anankastia domain and perfectionistic-type symptomatology given the addition of the Compulsivity (CMP) scale, which emerged as the best predictor of Anankastia domain scores, showing meaningful associations with individual CAT-PD traits such as Perfectionism, Rigidity and Workaholism, and thus being the main differential indictor of Anankastia from Negative Affectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, only Anderson and Sellbom's (2021) study was explicitly designed to examine the validity of the MMPI-2-RF whereas the other studies focused on validating various measures of the ICD-11 trait model. Anderson and Sellbom (2021) used a sample of community-dwelling individuals overweighted toward psychopathic and externalizing tendencies. Their results showed generally expected correlations between most hypothesized MMPI-2-RF scales and ICD-11 personality trait domains (e.g., Negative Affectivity with Emotional/Internalizing Dysfunction [EID], Demoralization [RCd] and Negative Emotionality/ Neuroticism [NEGE-r]; Dissociality and Disinhibition with various MMPI-2-RF externalizing scales).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the MMPI-2-RF/MMPI-3 can capture traditional PDs (e.g., Brown & Sellbom, 2021), including a set of PD spectra scales (Sellbom, Waugh, & Hopwood et al, 2018). The Personality Psychopathology Five scales directly assess the five domains of the DSM-5-TR Alternative Model of Personality Disorder (AMPD) and four of the five domains of the ICD-11 PDs (Anderson & Sellbom, 2021). The PAI has scales dedicated to the assessment of antisocial and borderline personality features and can also index the AMPD trait model (Ruiz et al, 2018).…”
Section: Assessment Of Response Bias With Omnibus Personality and Psy...mentioning
confidence: 99%
“…Bach et al (2017) created and investigated an algorithm for the PID-5, which allowed the user to compute a separate ICD-11 trait domain of anankastia by averaging the facet scores for “rigid perfectionism” and “perseveration.” This operationalization has been empirically supported and further refined in later studies (Bach et al, 2018; Fang et al, 2021; Hemmati et al, 2021; Lotfi et al, 2018; Lugo et al, 2019; Sellbom et al, 2020). Additionally, other well-established instruments such as Minnesota Multiphasic Personality Inventory and computerized adaptive test of personality disorders may also be used to delineate aspects of ICD-11 trait domains (Anderson & Sellbom, 2021; Tarescavage & Menton, 2020). As the first official measure of ICD-11 trait domains, Oltmanns and Widiger (2018) developed the 60-item Personality Inventory for ICD-11 (PiCD) capturing the five trait domains and the 121-item Five-Factor Personality Inventory for ICD-11 (FFiCD), which also captures 20 facets and 47 nuances (Oltmanns & Widiger, 2018, 2020).…”
Section: Measuring the Ampd And Icd-11 Trait Modelsmentioning
confidence: 99%